Tricarbocyanine N-triazoles: the scaffold-of-choice for long-term near-infrared imaging of immune cells in vivo. Issue 36 (8th August 2018) - Mellanby, Richard J.; Scott, Jamie I.; Mair, Iris; Fernandez, Antonio; Saul, Louise; Arlt, Jochen; Moral, Monica; Vendrell, Marc
Abstract : Tricarbocyanine N -triazoles are first described as rationally-designed structures to overcome the limitations of NIR dyes for long-term in vivo imaging. Abstract : Herein tricarbocyanine N -triazoles are first described as a rationally-designed near-infrared (NIR) structure overcoming the brightness and photostability limitations of tricarbocyanines for long-term in vivo imaging. The straightforward synthetic approach and the wide availability of alkynes makes this strategy a versatile methodology for the preparation of highly stable N -substituted tricarbocyanines. Furthermore, we validatedCIR38M as a non-transferable marker to monitor the fate of therapeutic T cells non-invasively in vivo, showing enhanced performance over conventional NIR fluorophores ( i.e. DiR, IR800CW and indocyanine green) as well as compatibility with human cells for translational studies.CIR38M is able to track over time smaller numbers of T cells than current NIR agents, and to visualise antigen-driven accumulation of immune cells at specific sites in vivo . This chemical technology will improve longitudinal imaging studies to assess the efficacy of cell-based immunotherapies in preclinical models and in human samples.